2008
DOI: 10.2967/jnumed.108.051599
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Angiogenesis-Related Gene Expression on the Tracer Kinetics of18F-FDG in Colorectal Tumors

Abstract: 18 F-FDG kinetics are primarily dependent on the expression of genes associated with glucose transporters and hexokinases but may be modulated by other genes. The dependency of 18 F-FDG kinetics on angiogenesis-related gene expression was evaluated in this study. Methods: Patients with primary colorectal tumors (n 5 25) were examined with PET and 18 F-FDG within 2 days before surgery. Tissue specimens were obtained from the tumor and the normal colon during surgery, and gene expression was assessed using gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 11 publications
1
47
0
Order By: Relevance
“…Several investigators have recently reported that the size of the metastatic lymph node is one of the strongest prognostic factors in esophageal cancer (27)(28)(29). Moreover, higher SUV max values indicate a higher malignant potential of cancer cells through a variety of mechanisms, such as cell proliferation, tissue hypoxia and angiogenesis (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have recently reported that the size of the metastatic lymph node is one of the strongest prognostic factors in esophageal cancer (27)(28)(29). Moreover, higher SUV max values indicate a higher malignant potential of cancer cells through a variety of mechanisms, such as cell proliferation, tissue hypoxia and angiogenesis (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of kinetic parameters may help to differentiate between benign and less aggressive tumors (e.g., lipomas from low-grade liposarcomas) (6). In a recent paper, we demonstrated a correlation between k 1 and angiogenesis-related genes (7). Based on dynamic datasets, parametric imaging can be applied using different algorithms.…”
Section: Replymentioning
confidence: 96%
“…In lung cancer, dynamic 18 F-FDG imaging followed by kinetic analysis has been shown to assist in differentiation between squamous cell carcinoma and adenocarcinoma, revealing differences in kinetics between these subtypes [8]. In colorectal tumours, kinetic analysis may help to differentiate between primary tumours and normal tissue [9], and kinetic parameters may provide information on proliferation and angiogenesis [10,11]. The literature contains a multitude of studies highlighting the potential significance of kinetic modelling in clinical oncology and drug development, as several critical reviews have shown [12][13][14].…”
Section: Introductionmentioning
confidence: 99%